Proses Evaluasi Kinerja Pada Department Human Resource Development (HRD) dan Administrasi Engineering Swiss-Belhotel Silae Palu - Rianto Hermawan; Moh Ali Murad; Wiri Wirastuti (Journal of Management and Social Sciences, 2023)
One of the supporters of the Ministry of Tourism and Creative Economy in improving the economy, especially in the field of tourism destinations, namely the Hospitality Industry. The main objective of the hospitality industry is as a means of accommodation for temporary accommodation for guests who come from various places. In competing in the hotel industry, a strong management structure is needed, especially in the human resources (HR) department. The implementation method is carried out through the dedication and assistance method in the Human Resource Development (HRD) and Engineering Administration departments. The results obtained show that the role of the Department of Human Resource Development (HRD) and the Department of Engineering in the hotel industry is an effort to improve the performance and quality of the performance of its employees because they play an important role in the hospitality industry, which aims to increase the productivity of the company's work, because a company can to develop and progress, of course, not only due to capital factors and a strong business strategy, but also great human resources (HR) and also fixing facilities if something is damaged or has an error.